Morte súbita e parada cardíaca em corredores de maratona: taxas de incidência e causas - Santos Targino de Araújo, O. A.; Carvalho Tenório, M. C. (Revista Brasileira de Fisiologia do Exercisio, 2020)
Introduction: The marathon race is an aerobic sport that requires high training volume. Marathon runners may eventually be exposed to unfavorable environmental conditions associated with changes in blood volume and hydration level that may increase the risk of cardiac arrhythmias that can cause cardiac arrest and sudden death. Objective: To identify the existing life risks for marathon runners related to the occurrences of sudden death and cardiac arrest and the most prevalent causes of these events. Methods: Integrative literature review of descriptive-qualitative nature in the databases: Google, Academic Google, Medline, Scielo and Pubmed. Results: Sudden death incidence rates ranged from 0.75 to 2.0 per 100.000 runners while cardiac arrest rates ranged from 1.01 to 2.6 per 100.000 runners being men most susceptible to these events. Among the causes of sudden death and cardiac arrest, studies indicate that in older athletes (age > 45 years) coronary artery disease (CAD) is the most prevalent and in younger athletes (age < 45 years) structural and congenital causes are the most common as hypertrophic cardiomyopathy. Most of the events of sudden death and cardiac arrest occurred in the last quartile of the race or after the finish line. Conclusion: The risks of sudden death and cardiac arrest in marathons are low and higher in men being coronary artery disease and hypertrophic cardiomyopathy the most prevalent causes of these events.